B.-Y. Chen Inequalities for Slant Submanifolds in Kenmotsu Space Forms II - Costache, Simona (Sarajevo Journal of Mathematics, 2024)
In this article, we investigate sharp inequalities involving Chen invariants for a slant submanifold $M$ of a Kenmotsu space form $\widetilde{M}(c)$, tangent to the structure vector field of the ambient space. 2000 Mathematics Subject Classification. 53C40, 53C25